PRIMARY CARE APPROACHES TO PREVENTING TYPE 2 DIABETES MELLITUS IN ADULTS - Vanevenhoven, Danielle L. (My University, 2010)
Type 2 diabetes mellitus is a progressive metabolic disorder of the endocrine system, characterized by a natural progression of insulin resistance and impaired insulin secretion. Due to the slow and gradual onset of symptoms, most individuals are unaware they have diabetes until subsequent complications surface and they are diagnosed (Uphold & Graham, 2003). Type 2 diabetes is reaching epidemic proportions in the Western culture. At the turn of the century, it was estimated that approximately 150 million people worldwide had type 2 diabetes mellitus; this number is projected to double by the year 2025 (Boylan, 2006). The purpose of this study was to explore how primary healthcare providers (physicians, nurse practitioners) identify and intervene with risk-reduction behaviors with adults at risk for developing type 2 diabetes mellitus. Pender's (2006) Health Promotion Model (HPM) served as the theoretical framework for this study. This model integrates nursing and behavioral science perspectives with concepts that influence health-promoting behaviors. A descriptive qualitative design was used to conduct the study. Participants included a convenience sample of eight physicians and two nurse practitioners from a primary healthcare facility in Northeast Wisconsin. Data were collected through tape recorded interviews using open-ended questions to explore how primary healthcare providers identified and intervened with risk-reduction behaviors in adults at risk for developing type 2 diabetes mellitus. The interviews were then transcribed verbatim and used for data analysis. Colaizzi's method was used to extract meaningful statements describing the participant's experience (Polit & Beck, 2008). The data were further organized into the following themes: (a) Identification: Who Is at Risk, (b) The Intervention: What Do We Need to Do, (c) Establishing Consistency: Continuing to Build Support, and (d) Extenuating Circumstances. The emerging themes are meant to validate the participants' descriptions of how they identified and intervened with at-risk adults. The findings of this study will be compiled into a brief handout that will be dispersed to the primary healthcare providers at the healthcare facility in Northeast Wisconsin, where the sample was obtained. The handout is intended to provide additional education and support to healthcare providers to further assist in identifying and providing interventions that reduce the risk of developing type 2 diabetes in adults.
A Clinical Paper Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science in Nursing Family Nurse Practitioner
Keywords: Low carbohydrate diet; Non-insulin dependent diabetes; Health risk assessment; Exercise Health aspects